Preparation and characterization of in(OH)3: Eu nanostructures obtained by microwave-assisted hydrothermal method - Motta, Fabiana V.; Marques, Ana Paula A.; Paskocimas, Carlos A.; Bomio, Mauricio R. D.; Abreu, Maria Fernanda C.; Li, Máximo S.; Leite, Edson R.; Varela, José A. [UNESP]; Longo, Elson [UNESP] (My University, 2012)
Crystalline europium-doped indium hydroxide (In(OH)3:Eu) nanostructures were prepared by a rapid and efficient Microwave-Assisted Hydrothermal (MAH) method. Nanostructures were obtained at a low temperature. FE-SEM images confirm that these samples are composed of 3D nanostructures. XRD, optical diffuse reflectance and photoluminescence (PL) measurements were used to characterize the products. Emission spectra of europium-doped indium hydroxide samples under excitation (350.7 nm) presented broad band emission referent to the indium hydroxide (In(OH)3) matrix and 5D0→7F0, 5D0→ 7F1, 5D0→ 7F2, 5D0→ 7F3 and 5D0→ 7F4 europium transitions at 582, 596, 618, 653 and 701 nm, respectively. Relative intensities of the Eu3+ emissions increased as the concentration of this ion increased from 0, 1, 2, 4 and 8 mol %, of Eu3+, but the luminescence is drastically quenched for the In(OH)3 matrix. © 2012 by Nova Science Publishers, Inc. All rights reserved.
Keywords: Hydrothermal; Hydroxide; Indium; Microwave; Nanostructures